The Inventory of Legal Knowledge (ILK) and adults with intellectual disabilities. Issue 2 (12th June 2017) - Watson, Malorie E.; Kivisto, Aaron J.
Abstract : Purpose: Adults with intellectual disabilities (ID) entering the legal system in the USA are at heightened risk of being incorrectly labeled as malingering. The Inventory of Legal Knowledge (ILK) was recently developed to assess response style of individuals undergoing competency to stand trial (CST) evaluations. The purpose of this paper is to present preliminary data on the utility of the ILK with adults with ID. Design/methodology/approach: In total, 32 adults were recruited from an American day program for adults with ID. Using a simulation design, the first 24 participants were assigned to the honest responding group and the remaining eight were assigned to the fake bad group. The normative performance of the honest responding group was compared to established norms for adults without ID, the most efficient ILK cut-off score was examined, and convergent validity of the ILK and other malingering measures tested. Findings: Compared to the established mean score, the recommended cut-off score, and two independent published samples of non-ID adults, the normative performance of the honest responding ID group was significantly lower. Analyses of area under the curve revealed that the ILK lacked sufficient ability to discriminate adults with ID instructed to respond honestly from those instructed to feign incompetence, and correlational analyses failed to support the convergent validity of the ILK in this sample. Research limitations/implications: The present findings do not support the use of the ILK with adults with ID, even with adjusted cut scores. The development of novel malingering measures that can be used in the context of CST evaluations with adults with ID is needed. Originality/value: The present study is the first to examine the psychometric properties of the ILK with adults diagnosed with ID and without concomitant psychiatric symptomatology.